Rescher studies : a collection of essays on the philosophical work of Nicholas Rescher - Almeder, Robert F. (Reading Rescher ;, 2008)
In a career extending over almost six decades, Nicholas Rescher has conducted researches in almost every principal area of philosophy, historical and systematic alike. In this extraordinary volume, two dozen scholars join in offering penetrating discussions of various facets of Rescher's investigations. The result is an instructively critical panorama of the many-faceted contributions of this important American philosopher. Born in Germany in 1928, Nicholas Rescher came to the U.S. at the age of nine. He is University Professor of Philosophy at the University of Pittsburgh where he has also se.